Three-dimensional ordered macroporous Ru-substituted BaZrO3 perovskites: active catalysts for ammonia synthesis under mild conditions. Issue 22 (18th October 2019) - Li, Lingling; Yang, Linlin; Zhang, Tianhua; Wang, Xiuyun; Zhang, Xing; Lin, Bingyu; Ni, Jun; Dai, Hongxing; Au, Chak-Tong; Jiang, Lilong
Abstract : Three-dimensional ordered macroporous (3DOM) BaZr(1− x ) Ru x O3 perovskites were prepared by a PMMA-templating strategy and applied for ammonia synthesis for the first time. Abstract : Three-dimensional ordered macroporous (3DOM) BaZr(1− x ) Ru x O3 perovskites were prepared by a PMMA-templating strategy and applied for ammonia synthesis for the first time. The 3DOM BaZr(1− x ) Ru x O3 catalysts have a periodic macroporous structure and Ru species are dispersed in the well-arranged pores. The 3DOM BaZr0.95 Ru0.05 O3 catalyst shows effective ammonia synthesis under mild conditions. As proved by XAFS analysis, the active sites are surface Ru 0 clusters. It was demonstrated that 3DOM BaZrO3 is superior to S–G BaZrO3 that was prepared by a sol–gel method in ammonia synthesis at low temperature. This phenomenon is attributed to the small crystalline size and the well-arranged macroporous structure of the former.